The effects of exercise on sleep disturbances and cancer‐related fatigue for female breast cancer survivors receiving adjuvant hormone therapy: A systematic review - Anna Rose McGrorry; Amy Paterson; Nicola Peddie (Wiley, 2023)
Abstract Background Breast cancer is the most common type of cancer, accounting for 15% of all new cases. Hormone therapy (HT) is extremely effective in reducing breast cancer recurrence. However, adherence to HT medication is often poor due to negative side effects such as fatigue and sleep disturbances. Physical activity has been identified as a possible intervention to improve quality of life and reduce side effects of HT. Objective The objective of this systematic review was to summarise evidence of exercise interventions for women being treated with HT for breast cancer. Method Electronic searches were conducted from inception to March 2022 using Medline, SPORTdiscus, Embase, Scopus, PsycINFO and Web of Science databases. Searches included a combination of terms related to breast cancer, exercise, sleep disturbances, fatigue and HT. Results Ten eligible papers were identified, and their quality was assessed. Type, frequency, duration and intensity of exercise interventions varied. Exercise types included aerobics, strength/resistance training, walking and yoga. Heterogeneity of data made it difficult to draw conclusions. However, aerobic exercise interventions provide clear improvements in fatigue and sleep disturbances. Conclusions This review identified a lack of consistency in exercise recommendations for women being treated for breast cancer. It identifies that aerobic exercise can successfully improve fatigue and sleep disturbances, consistent with existing literature. Exercise has a range of benefits for this population, including improving psychological well‐being and quality of life. Clinicians should strongly advocate for engagement in exercise to promote overall physical and psychological well‐being in women being treated for breast cancer.